The Academic Background of Youth Soccer Coaches Modulates Their Behavior During Training - Agustí, David; Ballester, Rafael; Juan-Blay, Jordi; Taylor, William G.; Huertas, Florentino (Frontiers in Psychology, 2020)
This investigation aims to explore the relationship between the academic backgrounds of youth soccer coaches (U10 and U12 age groups) in Spain and the type of verbal behavior used during training sessions. The sample consisted of 70 coaches divided into two groups, depending on whether or not they had engaged with university-level academic studies related to Physical Education and or Sport Sciences. A modified version of the "Coach Analysis and Intervention System" (CAIS), developed by Cushion et al. (2012), was used to collect data. A total of 32,886 verbal behaviors were noted and analyzed. Our results suggest that the coaches with university academic backgrounds frequently use more verbal behaviors and that these could be associated with positive effects on the players’ learning and their development processes. We suggest it is important to develop specific training programs aimed at optimizing coaches’ communicative and socio-affective skills in order to maximize their impact in youth athletes’ learning process.